2009
DOI: 10.1039/b9nr00106a
|View full text |Cite
|
Sign up to set email alerts
|

UV-assisted capillary force lithography for engineering biomimetic multiscale hierarchical structures: From lotus leaf to gecko foot hairs

Abstract: This feature article provides an overview of the recently developed two-step UV-assisted capillary force lithography and its application to fabricating well-defined micro/nanoscale hierarchical structures. This method utilizes an oxygen inhibition effect in the course of UV irradiation curing and a two-step moulding process, to form multiscale hierarchical or suspended nanobridge structures in a rapid and reproducible manner. After a brief description of the fabrication principles, several examples of the two-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 56 publications
2
69
0
Order By: Relevance
“…In our experiment, the hydrophilic PUA 34,35 was mostly used as upper and lower moulds in order to replicate the hydrophobic PFPE resins [38][39][40] ; the materials can be swapped to obtain the exposed PFPE pillars with the background of the dewetted PUA domain (Fig. 1b).…”
Section: Resultsmentioning
confidence: 99%
“…In our experiment, the hydrophilic PUA 34,35 was mostly used as upper and lower moulds in order to replicate the hydrophobic PFPE resins [38][39][40] ; the materials can be swapped to obtain the exposed PFPE pillars with the background of the dewetted PUA domain (Fig. 1b).…”
Section: Resultsmentioning
confidence: 99%
“…We observed that the nano scale bubbles formed are slowly dissolved in PDMS and resin and finally disappear within about 30 min depends on dimensions of microstructures. By filling the mold with a resin that has a different level of dissolved oxygen compared to PDMS (Jeong et al 2009), diffusion and dissolving of O 2 resume again in direction of gradient until a saturation point reaches depends on chemical composition of the substrate.…”
Section: Physics Of the Problemmentioning
confidence: 99%
“…The UV-curable PUMA has been used in casting of the arrays of pillars using solid silicon and elastomeric PDMS molds by employing a source of UV radiation with pre-defined intensity for polymerization process (Alvankarian and Majlis 2012;Jafar and Burhanuddin Yeop 2015). Inhibition of polymerization of the UV-curable materials such as PUA by oxygen trapped or permeated through mold into the resin during casting and curing has been demonstrated and used for microfabrication of hierarchical structures by UV-assisted capillary force lithography (Jeong et al 2009), also for irreversible bonding of microchannels (Jeong 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the hierarchical adhesive surface could be made in a single casting process, by using microfabricated hierarchical fi ber molds. [ 30,32 ] Such molds should allow pillars with a diameter as small as 50 µm at least. [ 32 ] Also, the mesh could be microfabricated, e.g.…”
mentioning
confidence: 99%